Tarlov cyst: the disease that at some time neurologists forgotten (Research, Society and Development, 2022)
Tarlov's Cyst is a rare, mostly asymptomatic disease, and when symptomatic, it is responsible for causing neuropathic pain, resulting from nerve compression. The cyst is most commonly located in the sacral region, but its symptoms do not correspond to its origin, thus causing a certain disbelief and disparity among professionals, and for years a certain negligence towards patients with the disease. Another factor that has made the support of these individuals even more difficult is the scarcity of medical scholars in the area, as well as the lack of consensus on the appropriate therapeutic conduct. The objective of this article is to present a case report of a patient with the disease and to analyze the bibliography, with the purpose of contributing to the theoretical arsenal of the disease. Also present in this study are the history of the discovery of the cyst, its location, symptoms, causes, and existing treatments. The patient in question was included in the research because she had symptoms and a diagnosis of Tarlov's Cyst, and her case report was collected through a face-to-face interview. At the end of this article it was concluded that just like the patient in question, there are many cases in which patients seek a cure and find only temporary relief from pain, without a definitive cure, and it was shown how necessary it is to continue research and updates for professionals and students in the area.